Systematic analysis of photo/sko-regulated germination and post-germination development of shallow photodormant seeds in Nicotiana tabacum L. - Liu, Qiyuan; Li, Zhenhua; Zhang, Min; Dong, Shuai; Yang, Pingping; Zhang, Jie; Loades, Eddison (Frontiers in Plant Science, 2023)
Introduction Light is a major environmental factor in regulating germination and post-germination development of shallow photo-dormant seeds in Nicotiana tabacum L. (tobacco). However, its molecular mechanism remains largely unclear. Methods and results In this study, we compared the phenotypes of the seeds germinated under light and dark, and systematically investigated their regulatory networks by integrating transcriptomic and proteomic data. Under light, the germination increased ~25%, the length of the hypocotyl shortened ~3 cm, and the apical hook disappeared. 9, 161, 342 differentially expressed genes (DEGs) and 128, 185, 81 differentially expressed proteins (DEPs) were regulated by light in the development stage of seed imbibition, radicle protrusion and cotyledon expansion respectively. 0, 19 and 1 co-up-regulated and 1, 30 and 64 co-down-regulated DEGs (DEP) were observed in the three stages, respectively. Of them, 2S albumin large chain, was down-regulated by light in imbibed seed. Oleosin 18.5 kDa (OLEO1) and Glyceraldehyde-3-phosphate dehydrogenase (GAPA1), Oxygen-evolving enhancer protein 1-1 and anchloroplastic (PSBO1), hub genes (proteins) in protein-protein interaction network (PPI), were downregulated and up-regulated in germinated seeds by light, respectively. OLEO1, a hub gene (proteins), was down-regulated by light in post-germination seedling. Conclusion These results systematically revealed the molecular networks regulated by light during germination and post-germination development of shallow photo-dormant tobacco seeds.